An Ultra-High Field Magnetic Resonance Spectroscopy Study of Post Exercise Lactate, Glutamate and Glutamine Change in the Human Brain - Dennis, Andrea; Thomas, Adam G.; Rawlings, Nancy B.; Near, Jamie; Nichols, Thomas E.; Clare, Stuart; Johansen-Berg, Heidi; Stagg, Charlotte J. (Frontiers in Physiology, 2015)
During strenuous exercise there is a progressive increase in lactate uptake and metabolism into the brain as workload and plasma lactate levels increase. Although it is now widely accepted that the brain can metabolise lactate, few studies have directly measured brain lactate following vigorous exercise. Here, we used ultra-high field Magnetic Resonance Spectroscopy of the brain to obtain static measures of brain lactate, as well as brain glutamate and glutamine after vigorous exercise. The aims of our experiment were to (a) track the changes in brain lactate following recovery from exercise and, (b) to simultaneously measure the signals from brain glutamate and glutamine. The results of our experiment showed that vigorous exercise resulted in a significant increase in brain lactate. Furthermore, both glutamate and glutamine were successfully resolved, and as expected, although contrary to some previous reports, we did not observe any significant change in either amino acid after exercise. We did however observe a negative correlation between glutamate and a measure of fitness. These results support the hypothesis that peripherally-derived lactate is taken up by the brain when available. Our data additionally highlight the potential of ultra-high field magnetic resonance spectroscopy as a non-invasive way of measuring multiple brain metabolite changes with exercise.